Combined phylogenetic and morphometric information to delimit and unify the Triatoma brasiliensis species complex and the Brasiliensis subcomplex - Oliveira, Jader [UNESP]; Marcet, Paula L.; Takiya, Daniela M.; Mendonça, Vagner J.; Belintani, Tiago [UNESP]; Bargues, Maria D.; Mateo, Lucia; Chagas, Vivian; Folly-Ramos, Elaine; Cordeiro-Estrela, Pedro; Gurgel-Gonçalves, Rodrigo; Costa, Jane; et al. (Elsevier, 2017)
“Triatoma brasiliensis species complex” was defined as a monophyletic group of the species: T. brasiliensis, T. juazeirensis, T. melanica, and T. sherlocki. An alternative grouping scheme proposed the concept of “Brasiliensis subcomplex” which included the former species together with T. melanocephala, T. petrocchiae, T. lenti, T. tibiamaculata, and T. vitticeps. To evaluate the relationship among these taxa we combined the results obtained with four mitochondrial genes (12S, 16S, COI and Cytb, adding to 1811 bp) and geometric morphometric analysis of wings and heads. Panstrongylus megistus was included in the analysis as it was previously found related to T. tibiamaculata, T. melanocephala and T. vitticeps. The results of both molecular and morphometric approaches clearly grouped the species analyzed into two monophyletic units, supported by both genetic and wing variability. The first one (G1) comprises the four species originally included in the T. brasiliensis species complex plus T. lenti and T. petrocchiae. The second group (G2) was composed by T. melanocephala, T. tibiamaculata and T. vitticeps, and remarkably, P. megistus if considering wing variability and phylogenetic results. Nevertheless, geometric morphometrics of heads provided a quantitative measurement that discriminates Panstrongylus from the Triatoma species based on the position of the antennal insertion relative to eyes, as it is used as the generic distinctive character. The discrepancy among approaches questions the validity of this character to define Panstrongylus genus. Independently of the chosen group definition —“T. brasiliensis species complex” or “Brasiliensis subcomplex”—we propose to delimit it to species of G1 that are all associated with the Caatinga biome in the Brazilian Northeast. G2 are the ones associated with the Atlantic Forest biome.
Keywords: Genotype; Phenotype; Triatominae